Ecocentrism as Reconciliation of The Exploitation of Women and Nature by Capitalist Anthropocentrism: A Review of The Interpretation of Al-Tahrir wa Al-Tanwir - Juliani Syafitri; Siti Mariam Ulfah (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2024)
The concept of ecocentrism as a rehabilitation of the exploitation of nature and women becomes important in the midst of the onslaught of ecological disasters caused by the capitalist anthropocentrism of this era. Just as nature, women are among the victims because women and nature are often symbolized in similar ways in many respects. Ecocentrism plays a crucial role because it offers holistic justice for all elements of the natural world. The focus of this research is Ibn Asyur's interpretation in